Download presentation

Presentation is loading. Please wait.

Published byDebra Cannon Modified over 7 years ago

1
2.3 – Solving Multi-Step Equations

2
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21

3
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21

4
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p)

5
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p)

6
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) +

7
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) +

8
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8)

9
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8)

10
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21

11
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p

12
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56

13
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21

14
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21

15
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21

16
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56

17
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56 +56

18
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56 +56

19
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56 +56

20
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56 +56 -7p + 0 = 77

21
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56 +56 -7p + 0 = 77 -7p = 77

22
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56 +56 -7p + 0 = 77 -7p = 77 -7 -7

23
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56 +56 -7p + 0 = 77 -7p = 77 -7 -7

24
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56 +56 -7p + 0 = 77 -7p = 77 -7 -7 p = -11

25
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56 +56 -7p + 0 = 77 -7p = 77 -7 -7 p = -11 Ex. 2 -4(p - 5) = 12

26
Note: REVERSE Order of Operations! Ex. 1 -7(p + 8) = 21 -7(p) + -7(8) = 21 -7p - 56 = 21 + 56 +56 -7p + 0 = 77 -7p = 77 -7 -7 p = -11 Ex. 2 -4(p - 5) = 12 -4(p) – -4(5) = 12 -4p + 20 = 12 - 20 -20 -4p + 0 = -8 -4p = -8 -4 -4 p = 2

Similar presentations

© 2023 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google